The Importance of Fulfilling Nutrition for Pregnant Women and Toddlers in Stunting Prevention to Improve the Quality of Human Resources in Batu Ceper Village, Tangerang - Tekni Megaster; Fida Arumingtyas; Amelia Trisavinaningdiah (Asian Journal of Community Services, 2023)
Stunting is very influential on the development of growth and development as a determinant of the quality of human resources. Many factors include the lack of good nutrition, congenital and infectious diseases, ignorance of a mother's knowledge related to stunting, wrong parenting, poor hygiene handling and low environmental health services. Many people do not know and realize stunting children as a big problem. Because these stunted children in the midst of society look general and have normal activities. Seeing this problem, we have a goal to share information, knowledge and experience with the community, so that it is hoped that in the future the community will be able to avoid, overcome and prevent this stunting problem. The things achieved in this program are (a) residents have knowledge about stunting; (b) Regulate and maintain health in the family; (c) Printing of quality resources.